PEMICUAN JAMBAN SEHAT SEBAGAI SOLUSI BEBAS BUANG AIR BESAR SEMBARANGAN PADA MASYARAKAT KAMPUNG BULANG KOTA TANJUNGPINANG - Kholilah Samosir; Hendra Dhermawan Sitanggang (Jurnal Salam Sehat Masyarakat (JSSM), 2020)
The problem of open defecation (BABS) is still a public health problem in Tanjungpinang City. Based on data from the Health Office in 2018, there is no urban village that has ODF, including the people who live in the Kampung Bulang Urban Village. Most of them still throw their fists directly into the sea and some stills use swamps and drainage as places for defecation. It has become a habit for people to regard the sea as a giant septic tank, so they don't have to bother spending money to build proper disposal facilities. One of the efforts to reduce the number of open defecation, we made and installed latrines and septic tanks in the coastal area of Kampung Bulang Urban Village RW 10 RT 1, Tanjungpinang City.